2013
DOI: 10.1111/dmcn.12372
|View full text |Cite
|
Sign up to set email alerts
|

Is constraint‐induced movement therapy harmful in unilateral spastic cerebral palsy with ipsilateral cortico‐spinal projections?

Abstract: Constraint-induced movement therapy (CIMT) has become a well-established treatment for patients with hemiplegia, not only after stroke, but also in unilateral spastic cerebral palsy (USCP). In fact, most centers treating children and adolescents with this disorder offer CIMT. Numerous studies showed a good effect of CIMT in various cohorts of patients with USCP, but with considerable variability. Therefore, one would wish to be able to predict the response to CIMT in individual patients, especially since other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Our findings add to the existing literature on the influence of CST connectivity pattern on the efficacy of hand therapy. Although this literature is equivocal and had small samples, there seems to be some evidence that CIMT is more effective for children with a contralateral than for children with an ipsilateral CST 9,13 (in a homogeneous subpopulation of children with USCP 40 ). Our study suggests that this is not the case for bimanual therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings add to the existing literature on the influence of CST connectivity pattern on the efficacy of hand therapy. Although this literature is equivocal and had small samples, there seems to be some evidence that CIMT is more effective for children with a contralateral than for children with an ipsilateral CST 9,13 (in a homogeneous subpopulation of children with USCP 40 ). Our study suggests that this is not the case for bimanual therapy.…”
Section: Discussionmentioning
confidence: 95%
“…However, whether or not ipsilateral “re-wiring” forms the basis for differential treatment responses remains a topic of debate ( 66 ). While some authors have suggested that children with unilateral CP with pure ipsilateral control are poor responders to intensive unimanual training ( 61 , 67 ), others could not confirm these findings ( 68 ).…”
Section: Experimental Evidence Supporting the Categorization Based Onmentioning
confidence: 99%
“…While some authors have suggested that children with unilateral CP with pure ipsilateral control are poor responders to intensive unimanual training ( 61 , 67 ), others could not confirm these findings ( 68 ). These discrepancies reflect an on-going debate of how to determine the optimal therapy for the individual child with CP ( 48 , 66 ). Additionally, the impact of the wiring pattern with respect to therapy outcome following different programs, i.e., bimanual training vs. intensive unimanual training, has not yet been systematically investigated.…”
Section: Experimental Evidence Supporting the Categorization Based Onmentioning
confidence: 99%
“…[11][12][13]18 Contralateral reorganization, in turn, has been associated with greater treatment efficacy than ipsilateral reorganization. 27,28,30 A possible neurophysiological mechanism that may account for such an association relates to the concept of "hemispheric dissociation." The primary somatosensory representation (S1) of the affected hand is typically preserved in the affected hemisphere in both types of cortical-spinal tract reorganizations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of consistent study findings regarding the factors that can predict treatment outcomes in this population, a call has been issued for further research to enable the development of optimally beneficial and individually tailored interventions. 30 Previously, these authors performed a single-blinded, randomized controlled trial that revealed a significantly large and equal improvement in hand function among infants following both m-CIMT and bimanual therapy, accompanied by large within-group variability. The authors found that factors such as Apgar scores, gestational age, birth weight, age, hours of treatment, and baseline scores on the mini-Assistive Hand Assessment (Mini-AHA) did not contribute toward the prediction of upper extremity treatment outcomes.…”
mentioning
confidence: 99%